A novel grey projection incidence model for assessing the relationships between cardiovascular diseases and air pollutants. (April 2023) - Feng, Yu; Dang, Yaoguo; Wang, Junjie; An, Yimeng
Abstract: The accurate assessment of the relationships between cardiovascular diseases and various air pollutants is essential for population health protection, especially in low- and middle-income countries or regions with poor air quality and dense populations. In view of this situation, we propose a novel grey incidence model, namely, the grey projection incidence model based on Gaussian function, by integrating the advantages of geometric projection and Gaussian function. Firstly, the basic principles of the proposed model are elaborated. Then, a framework including six steps to evaluate the relationships between CVDs and air pollutants is illustrated. Finally, a case study is utilized to validate the effectiveness of the proposed model. Experimental results show that the proposed model outperforms other grey incidence models in terms of reliability and stability of the relational rank. Highlights: A novel incidence model is proposed to assess CVDs-related air pollutants. The GPIMG has no restrictions on the distribution or size of samples. The GPIMG integrates Gaussian function into grey incidence analysis. A real case is utilized to demonstrate the effectiveness of the proposed method. The case proves PM2.5 and PM10 are the key air pollutants causing CVDs in Tianjin.